Diploma Retention Clause in Employment Relationships: The Power Dynamics Between Employees and Employers: Klausula Penahanan Ijazah Dalam Hubungan Kerja: Relasi Kuasa Antara Pekerja dan Pengusaha - Olivia Grasera, Brenda; Haliza Yuniar, Putri; Pujiastuti, Endah; Arifin, Zaenal (Mendapo: Journal of Administrative Law, 2026)
This study aims to analyze the validity of the detention clause diploma by the company through the perspective of labor law and power relations theory. The phenomenon of diploma withholding is still found in the practice of Labor Relations in Indonesia, although it has no explicit legal basis in labor regulations and is often justified as a form of safeguarding the interests of the company. This practice reflects the inequality of positions between employers and workers, giving rise to an urgency to reassess its legal legitimacy within the framework of protecting the fundamental rights of workers. The research method used is juridical normative approach to legislation and conceptual. The results showed that the detention of diplomas is contrary to the principles of freedom of work, the principle of equality, and respect for human dignity as reflected in Law Number 13 of 2003 concerning manpower amended by Law Number 6 of 2023 concerning the establishment of government regulations in lieu of Law Number 2 of 2022 concerning job creation into law. The conclusion of the study confirms that the diploma withholding clause in the employment agreement is invalid and should have been declared null and void. The novelty of the study lies in the use of Michel Foucault's theory of power relations to explain the detention of diplomas as an instrument of control that maintains the structural dominance of employers over workers in modern industrial relations.